2023
DOI: 10.1515/med-2023-0666
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of lncRNA LANCL1-AS1 inhibits the progression of non-small-cell lung cancer via the miR-3680-3p/GMFG axis

Abstract: Patients with non-small-cell lung cancer (NSCLC) have a low survival rate. Long non-coding RNA (LncRNA) LANCL1 antisense RNA 1 (LANCL1-AS1) was indicated to be downregulated in NSCLC; however, its detailed function in NSCLC is unanswered. Real-time quantitative polymerase chain reaction revealed the downregulation of LANCL1-AS1 in NSCLC cell lines and subcellular fractionation assay showed that LANCL1-AS1 was mainly located in the cytoplasm of NSCLC cells. Cell counting kit-8, Transwell, and tube formation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Gan et al found that let-7d-5p expression was remarkably increased in LC cells treated with Trametes robiniophila, and its upregulation inhibited angiogenesis and tumor growth in LC by targeting NAP1L1 (134). Chang et al demonstrated that exosomal miR-197-3p from LUAD cells could facilitate the angiogenesis of HUVECs by directly downregulating TIMP2/3 (135). Furthermore, Pan et al discovered that LANCL1-AS1 upregulation dramatically repressed the angiogenesis of NSCLC cells by upregulating glia maturation factor gamma via sponging miR-3680-3p (136).…”
Section: Ncrna In Lc Angiogenesismentioning
confidence: 99%
“…Gan et al found that let-7d-5p expression was remarkably increased in LC cells treated with Trametes robiniophila, and its upregulation inhibited angiogenesis and tumor growth in LC by targeting NAP1L1 (134). Chang et al demonstrated that exosomal miR-197-3p from LUAD cells could facilitate the angiogenesis of HUVECs by directly downregulating TIMP2/3 (135). Furthermore, Pan et al discovered that LANCL1-AS1 upregulation dramatically repressed the angiogenesis of NSCLC cells by upregulating glia maturation factor gamma via sponging miR-3680-3p (136).…”
Section: Ncrna In Lc Angiogenesismentioning
confidence: 99%